Fox defecation behaviour in relation to spatial distribution of voles in an urbanized area: An increasing risk of transmission of Echinococcus multilocularis? - Robardet, Emmanuelle; Giraudoux, Patrick; Caillot, Christine; Augot, Denis; Barrat, Jacques (International Journal for Parasitology, 2010)
International audience Urbanization of alveolar echinococcosis is a new phenomenon that has been highlighted during the last few decades. It has thus become necessary to understand the dynamics of transmission of Echinococcus multilocularis in urbanized areas. Spatial heterogeneity of infection by E. multilocularis has been explained as the result of a multifactorial dependence of the transmission in which the factors depend on the scale of the investigation. The aim of this study was to assess, in an urbanized area, the effect of such environmental factors as season, habitat type and the level of urbanization, on the availability of two major intermediate hosts (Microtus spp. and Arvicola terrestris), the distribution of red fox faeces and the distribution of E. multilocularis as determined by detection of coproantigens in faeces. Results of the study revealed higher densities of Microtus spp. in rural than in peri-urban areas. Moreover this species was highly aggregated in urban wasteland. Arvicola terrestris densities did not appear to be linked to the level of urbanization or to the type of habitat studied. Distribution of faeces was positively linked to distance walked and to Microtus spp. and A. terrestris distributions whatever the level of urbanization. Such a distribution pattern could enhance the transmission cycle in urban areas. The Copro-ELISA test results on faeces collected in the field revealed that O.D.s were significantly negatively correlated with the abundance of A. terrestris. The larger population densities of Microtus spp. found in urban wastelands and the well known predominance of Microtus spp. in the red fox diet in the region suggest that Microtus spp. may play a key-role in urban transmission of the parasite in the study area.